Asbestos-related diseases in mineworkers: a clinicopathological study. Issue 3 (25th August 2017) - Ndlovu, Ntombizodwa; Rees, David; Murray, Jill; Vorajee, Naseema; Richards, Guy; teWaterNaude, Jim
The accurate diagnosis of asbestos-related diseases is important because of past and current asbestos exposures. This study evaluated the reliability of clinical diagnoses of asbestos-related diseases in former mineworkers using autopsies as the reference standard. Sensitivity, specificity, positive predictive value and negative predictive value were calculated. The 149 cases identified had clinical examinations 0.3–7.4 years before death. More asbestos-related diseases were diagnosed at autopsy rather than clinically: 77 versus 52 for asbestosis, 27 versus 14 for mesothelioma and 22 versus 3 for lung cancer. Sensitivity and specificity values for clinical diagnoses were 50.6% and 81.9% for asbestosis, 40.7% and 97.5% for mesothelioma, and 13.6% and 100.0% for lung cancer. False-negative diagnoses of asbestosis were more likely using radiographs of acceptable ( versus good) quality and in cases with pulmonary tuberculosis at autopsy. The low sensitivity values are indicative of the high proportion of false-negative diagnoses. It is unlikely that these were the result of disease manifestation between the last clinical assessment and autopsy. Where clinical features suggest asbestos-related diseases but the chest radiograph is negative, more sophisticated imaging techniques or immunohistochemistry for asbestos-related cancers should be used. Autopsies are useful for the detection of previously undiagnosed and misdiagnosed asbestos-related diseases, and for monitoring clinical practice and delivery of compensation. Asbestos-related diseases are difficult to diagnose; 58% diagnosed at autopsy had been missed clinically http://ow.ly/L9u230dr0bv